The onset factors towards adolescents premarital sexual intercourse / Khairiyah Hj. Md. Shahid … [et al.] - Md. Shahid, Khairiyah; Abu Bakar Ah, Siti Hajar; Abd. Wahab, Haris; Omar, Noralina; Jasni, Mohd Alif (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Sexuality is a very sensitive topic to discuss openly for some society. In regards to the Islamic rules and values, the issue of premarital sexual intercourse is prohibited within the Muslim society. This study intends to comprehend the onset and contributing factors of Malay adolescent girls’ decision making towards engaging in premarital sexual intercourse. Methodologically, semi-structured interviews were conducted in this study to understand about Muslim young girls’ sexual decision-making out of wedlock. The results of a qualitative data are present and discussed. Data analysis shows that their involvements with premarital sex issues categorized into two broad spectrums: personal factors and social influences. Since issues of premarital sex can lead to many other social problems such as teenage and unwanted pregnancy, abortion as well as sexually transmitted diseases, therefore a serious intervention needs to be developed and closely monitored.